A randomized controlled trial to compare the safety and effectiveness of doxycycline (200 mg daily) with oral prednisolone (0·5 mg kg−1 daily) for initial treatment of bullous pemphigoid: a protocol for the Bullous Pemphigoid Steroids and Tetracyclines (BLISTER) Trial. (26th May 2015) - Chalmers, J.R.; Wojnarowska, F.; Kirtschig, G.; Nunn, A.J.; Bratton, D.J.; Mason, J.; Foster, K.A.; Whitham, D.; Williams, H.C.; the BLISTER study group; Williams, H.; Mason, J.; et al.
Summary Background Bullous pemphigoid (BP) is the most common autoimmune blistering disease in older people, and is associated with significant morbidity and mortality. Oral corticosteroids are usually effective but the side‐effects are thought to contribute to the high morbidity and mortality rate. Treatment with oral tetracyclines may be effective but high‐quality, randomized controlled trials (RCTs) are needed to confirm this. Objectives To compare the effectiveness and safety of two strategies for treating BP. Methods This is a two‐arm, parallel group, 52‐week RCT comparing doxycycline with prednisolone for initial treatment of BP. Dose is fixed for the initial 6 weeks of treatment (doxycycline 200 mg daily; prednisolone 0·5 mg kg−1 daily), after which it can be adjusted according to need. A total of 256 patients with BP will be recruited in the U.K. and Germany. Results The primary outcomes are: (i) effectiveness (assessor‐blinded blister count at 6 weeks) and (ii) safety [proportion of patients experiencing ≥ grade 3 adverse events (i.e. severe, life: threatening or fatal) related to trial medication during the year of follow‐up]. Primary effectiveness analysis will be an assessment of whether doxycycline can be considered noninferior to prednisolone after 6 weeks of treatment. Primary safety analysis is a superiority analysis at 12 months. Secondary outcomes include longer‐term assessment of effectiveness, relapse rates, the proportion of patients experiencing any grade of adverse events related to treatment, quality of life and cost‐effectiveness. Conclusions The trial will provide good evidence for whether the strategy of starting BP treatment with doxycycline is a useful alternative to prednisolone.